2020
DOI: 10.1002/rrq.361
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Cognitive Affective Engagement Model of Learning From Multiple Texts: A Structural Equation Modeling Approach

Abstract: Given limited work modeling the role of individual difference factors and processing variables in students’ learning from multiple texts, the author evaluates such a model. In particular, the model analyzed examines the relation between cognitive (i.e., habits with regard to information evaluation) and affective (i.e., interest) individual difference factors and multiple‐text outcomes (i.e., integrated mental model development and intertext model development, as facets of multiple‐text integration), as mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 110 publications
(149 reference statements)
2
9
0
Order By: Relevance
“…For example, Bråten et al (2014) found that both prior topic knowledge and interest in the topic were positively related to students' time use, with time use also mediating the effect of interest on their comprehension performance. Likewise, List (2020) found that behavioral engagement as indicated by time on task was affected by topic interest and thus mediated the effects of topic interest on comprehension performance, and List et al (2019) found that the time students devoted to text use mediated the effects of situational (i.e., text-based) interest on the written comprehension products. Moreover, List (2020) found that a cognitive factor based on students' scores on a general, decontextualized measure of perceived strategy use predicted the time devoted to text use and, in turn, their comprehension performance.…”
Section: Prior Researchmentioning
confidence: 97%
See 4 more Smart Citations
“…For example, Bråten et al (2014) found that both prior topic knowledge and interest in the topic were positively related to students' time use, with time use also mediating the effect of interest on their comprehension performance. Likewise, List (2020) found that behavioral engagement as indicated by time on task was affected by topic interest and thus mediated the effects of topic interest on comprehension performance, and List et al (2019) found that the time students devoted to text use mediated the effects of situational (i.e., text-based) interest on the written comprehension products. Moreover, List (2020) found that a cognitive factor based on students' scores on a general, decontextualized measure of perceived strategy use predicted the time devoted to text use and, in turn, their comprehension performance.…”
Section: Prior Researchmentioning
confidence: 97%
“…Likewise, List (2020) found that behavioral engagement as indicated by time on task was affected by topic interest and thus mediated the effects of topic interest on comprehension performance, and List et al (2019) found that the time students devoted to text use mediated the effects of situational (i.e., text-based) interest on the written comprehension products. Moreover, List (2020) found that a cognitive factor based on students' scores on a general, decontextualized measure of perceived strategy use predicted the time devoted to text use and, in turn, their comprehension performance. Both prior knowledge and topic interest were also positively related to indicators of behavioral engagement (e.g., number of unique websites visited and revisited) in the Kammerer et al (2021) study.…”
Section: Prior Researchmentioning
confidence: 97%
See 3 more Smart Citations